Sampling and statistical methods for behavioral ecologists - Bart, Jonathan (Cambridge University Press, 1998)
This book describes the sampling and statistical methods used most often by behavioral ecologists and field biologists.The first section reviews important issues such as defining the statistical population and the sampling plan when using nonrandom methods for sample selection, bias, interpretation of statistical tests, confidence intervals, and multiple comparisons. After a detailed discussion of sampling methods and multiple regression, subsequent chapters discuss specialized problems such as pseudoreplication, and their solutions.